2002
DOI: 10.1055/s-2002-21568-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Giant Cell Reparative Granuloma of the Skull Base and the Paranasal Sinuses Presenting with Acute One-Sided Blindness

Abstract: The etiology, pathogenesis, histopathologic diagnosis, prognosis, and treatment of giant cell reparative granulomas of the skull are controversial. We report a 14-year-old girl with an advanced recurrent giant cell reparative granuloma of the skull base and paranasal sinuses whose only clinical manifestation was a loss of vision. After undergoing endovascular catheter embolization, the patient underwent repeated surgical resections of the mass via a combined frontobasal and modified infratemporal approach foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Also, some cases have a more destructive nature. 3,7 Our case represents a rare finding of GCG occurring within the right temporal bone including attachments to the dura. This lesion was associated with CNS symptoms and was believed to be something more ominous.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Also, some cases have a more destructive nature. 3,7 Our case represents a rare finding of GCG occurring within the right temporal bone including attachments to the dura. This lesion was associated with CNS symptoms and was believed to be something more ominous.…”
Section: Introductionmentioning
confidence: 81%
“…1,2 Few cases of central GCG arise within the skull base. 3 There are several cases of GCG arising in the temporal bone. [4][5][6][7][8][9][10][11][12][13][14] Initially referred to as a "giant cell reparative granuloma," it is now more commonly referred to as "giant cell granuloma," This is due to the fact that the once perceived notion that the lesion represented an attempt to repair areas of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry and electron microscopy studies have confirmed that the macrophages responsible for repair are the precursors of the giant cells in GCRG, supporting the idea that GCRG can be caused by trauma and inflammation. 8,9,12 However, this hypothesis has been challenged by many other researchers because a considerable number of patients have no clear history of trauma and/or inflammation. [6][7][8] The two cases we report here had a clear history of skull base meningioma resection and otitis media and mastoiditis, supporting the trauma and inflammation theory of GCRG.…”
Section: Discussionmentioning
confidence: 99%
“…However, this theory is challenged by the fact that not all patients have a clear history of traumatic bleeding or inflammation. [6][7][8] In this communication, we report two cases of GCRG in the temporal bone of the skull base. One case had a history of previous tumor resection, and the other case had a history of chronic otitis media.…”
mentioning
confidence: 91%
“…Giant cell granuloma accounted for 7% of the maxillary tumors (Rubio-Correa et al 2012). Few cases of central GCG arise within the skull base (Plontke S K et al 2002).There There are several cases of GCG arising in the temporal bone (Yu J L et al 2010). It It is more common in children and young adults, with a slight predominance in females (Comert et al 2006).…”
Section: Introductionmentioning
confidence: 99%